Synbiotics as Treatment for Irritable Bowel Syndrome: A Review - Henning Sommermeyer; Jacek Piątek (Microorganisms, 2024)
Irritable bowel syndrome is a persistent disturbance of the function of the gastrointestinal tract with a prevalence of about 11.2% in the population at large. While the etiology of the disorder remains unclear, there is mounting evidence that the disturbance of the gut microbiota is at least one contributing factor. This insight resulted in clinical trials investigating the therapeutic effects of products containing probiotic microorganisms. Most studies with IBS patients have evaluated the therapeutic effects of mono- and multi-strain probiotics, but only a few studies have investigated the efficacy of synbiotics (combinations of probiotic bacteria and one or more prebiotic components). This review summarizes the results from eight randomized, placebo-controlled clinical trials that investigated the efficacy of synbiotic preparations (three mono-strain and five multi-strain products) in adult IBS patients. While data remain sparse, some of the surveyed clinical trials have demonstrated interesting efficacy results in IBS patients. To allow a judgment of the role played by synbiotics in the treatment of IBS patients, more high-quality clinical trials are needed.